In-Vitro Neutralization Efficacy of Taxifolin against Anthrax Toxins - Taskeen, Shumaila; Rawool, Deepak B; Aggarwal, Somya; Somani, Vikas; Bhatnagar, Rakesh (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The present study was undertaken to evaluate the protective efficacy of Taxifolin against anthrax toxins viz., lethal toxin (LT) and edema toxin (ET) in in-vitro model. The MTT assay and cAMP ELISA was deployed to estimate the LT induced cytoxicity and ET induced intracellular increase in cyclic AMP respectively, wherein 10μg PA +1μg LF/EF was deduced as the cytotoxic dose. The assays revealed an anticipated dose dependent decrease in cytotoxicity at varying concentrations (100μM to 0.1μM) of taxifolin when challenged against optimized cytotoxic dose of LT (10μg PA +1μg LF). Similar dose dependent decrease in intracellular cAMP levels was observed at all the evaluated concentrations of taxifolin (100μM to 0.1μM) against cytotoxic dose of ET (10μg PA +1μg EF). The neutralization potential of taxifolin against both the anthrax toxins pave a way for future prospects of experimentation using combination of taxifolin with other such inhibitors and/or antibiotics in in vitro and in vivo model, which could therefore be helpful in formulating therapeutics against anthrax.
Keywords: Anthrax; Lethal toxin; Edema toxin; Protective antigen; Taxifolin